Assessing social support and stress in autism-focused virtual communities emerging research and opportunities - Saha, Amit; Agarwal, Nitin (Advances in educational technologies and instructional design (AETID) book series, 2018)
"This book explores social support and stress in Autism-focused virtual communities. It covers topics such as autism and social media, social support and stress, social support assessment, and stress assessment"...